Maturation of the Locomotor Circuitry in Children With Cerebral Palsy - Cappellini, Germana; Sylos-Labini, Francesca; Dewolf, Arthur H.; Solopova, Irina A.; Morelli, Daniela; Lacquaniti, Francesco; Ivanenko, Yury (Frontiers in Bioengineering and Biotechnology, 2020)
The first years of life represent an important phase of maturation of the central nervous system, processing of sensory information, posture control and acquisition of the locomotor function. Cerebral palsy (CP) is the most common group of motor disorders in childhood attributed to disturbances in the fetal or infant brain, frequently resulting in impaired gait. Here we will consider various findings about functional maturation of the locomotor output in early infancy, and how much the dysfunction of gait in children with CP can be related to spinal neuronal networks vs. supraspinal dysfunction. A better knowledge about pattern generation circuitries in infancy may improve our understanding of developmental motor disorders, highlighting the necessity for regulating the functional properties of abnormally developed neuronal locomotor networks as a target for early sensorimotor rehabilitation. Various clinical approaches and advances in biotechnology are also considered that might promote acquisition of the locomotor function in infants at risk for locomotor delays.